The Recall and New Job Search of Laid-Off Workers: A Bivariate Proportional Hazard Model with Unobserved Heterogeneity - Fallick, Bruce; Ryu, Keunkwan (The Review of Economics and Statistics, 2007)
Workers who lose their jobs can become reemployed either by being recalled to their previous employers or by finding new jobs. Workers' chances for recall should depress their job search intensity, so the rates of exit from unemployment by these two routes should be negatively related. We look for evidence in the PSID data by estimating a semiparametric competing risks model with explicitly related hazards. Our estimates reveal a statistically precise but small negative effect of recall probabilities on the rate of new job finding.